Rational use of water and nitrogenated fertilization in corn (Zea mays l.) irrigated by dripping in autumn / winter cultivation - DA SILVA, Paulo Ferreira; Dos Santos, Marcos Antonio Liodoro; DE SOUZA, João Victor Ribeiro Da Silva [UNESP]; DA SILVA, Douglas Marcelo Pinheiro; Ferrari, Jéssica Maiara De Souza [UNESP]; Saad, João Carlos Cury [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2020)
This study was carried out to investigate the effect of irrigation and nitrogen fertilizer doses on the productivity of corn grown between April and October 2016 and 2017. The experiment was conducted at Fazenda Lageado in the experimental area located at geodetic coordinates 22°51'07 South, 48°25'45.07 West and altitude of 764 m. The soil was corrected with dolomitic limestone only in 2016 and the sowing carried out at a spacing of 0.85 x 0.20 m between the lines and plants, respectively, with the addition of 300 kg of NPK 04-30-10 applied in the furrow. The experimental design used was randomized blocks, in a 5 x 5 factorial scheme, with a subdivided plot with five levels of irrigation corresponding to 50, 75, 100, 125 and 150% of the daily culture evapotranspiration (ETc) and five doses of nitrogen fertilization at levels 0; 22.5; 45; 67.5 and 90 kg ha-1 of N, using urea as a source of N in four replications. The productivity of corn grains was higher using depth with 100% ETc in the years 2016 and 2017. For the nitrogen fertilization factor, the highest yield was obtained at the level using 90 kg ha-1 of N.
Uso racional da água e da adubação nitrogenada no milho (Zea mays l.) irrigado por gotejamento em cultivo de outono/inverno1
Keywords: Grain yield; Supplementary irrigation; Water saving